Electric vehicle technology impacts on energy - Wael A. Salah; Basim Alsayid; Mahmoud A. M. Albreem; Basem Abu Zneid; Mutasem Alkhasawneh; Anwar Al–Mofleh; Anees Abu Sneineh; Amir Abu Al-Aish (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
The CO2 emission level is becoming a serious issue worldwide. The continuous increase in gasoline price forms the essential base of development of electric vehicle (EV) drives. Moreover, economic and environmental issues relate to fabrication and operation of traditional powered vehicles. The basic considerations and development perspectives of EVs are presented in this paper. The development of an efficiently designed motor and drive satisfy the need of efficient characteristics that enable EVs to perform as part of the propulsion unit. The use of digital signal controllers compared with conventional control systems minimizes the motor’s total harmonic distortion, lowers operating temperatures, and produces high efficiency and power factor ratings. This paper addresses the view of EV technology as well its advantages over other technologies.